The Role of Community-Based Tourism in Achieving Justice and Sustainability in Indonesia’s Rural Areas (Indonesian Tourism Justice Review, 2025)
Community-based tourism (CBT) has emerged as a promising model for promoting social justice and environmental sustainability in Indonesia’s rural areas. This paper explores the role of CBT in empowering local communities, promoting cultural preservation, and ensuring fair economic benefits from tourism. Through case studies in regions such as Flores, Sumba, and Aceh, the research examines how CBT initiatives contribute to the social and economic development of rural communities by providing alternative livelihoods and fostering local ownership of tourism resources. The study evaluates the challenges faced by CBT projects, including limited access to capital, market competition, and the need for capacity-building among local stakeholders. Drawing on interviews with local entrepreneurs, community leaders, and tourism experts, the paper identifies the critical success factors that make CBT an effective tool for achieving both justice and sustainability. The paper concludes by offering recommendations for scaling up CBT initiatives across Indonesia, emphasizing the importance of government support, community engagement, and partnerships with ethical tourism operators.